Strategies Used by An English Teacher-Parent Toward Their Children's English Skills - Hanafi, Nurwahidah; Samtidar, Samtidar; Sakkir, Geminastiti (State University of Makassar, 2025)
The objective of this study was to identify the strategies employed by an English teacher who is also a parent in enhancing their children's English proficiency. The researcher utilized a descriptive qualitative approach, specifically employing a case study method. The subject of this research was an English teacher-parent at SMAN 3 Takalar. The researcher used an observation checklist and interviews as instruments to collect data in this research. Based on the findings of the researcher, the results indicate that the strategies used by an English teacher-parent: In terms of listening skills, a parent leveraged technology such as YouTube and educational apps to expose their children to English audio materials. It made learning enjoyable and accessible for children. In the context of reading skills, a parent emphasized the importance of providing age-appropriate and engaging reading material, such as English books, especially fairy tales. For writing skills, a parent incorporated writing into their child's daily routine by assigning typing tasks in English. Finally, the development of speaking abilities was fostered by establishing a home environment that embraced multiple languages. An English teacher-parent employed a multifaceted approach to enhance their children's English language skills. They leveraged technology, utilized age- appropriate reading materials, assigned writing tasks, and created a multilingual environment to foster well-rounded English language development.Keywords An English Teacher-Parent, Parenting Strategy, and English Skills.